Review of Trachysphaera Heller, 1858 (Diplopoda: Glomerida: Glomeridae) in Serbia, with taxonomic notes on the genus - Antić, Dragan; Šević, Mirko; Macek, Oliver; Akkari, Nesrine (Zootaxa, 2021)
The glomerid genus Trachysphaera Heller, 1858 in Serbia is revised, based on recently collected specimens and historical material. Six species are presently recorded from Serbia, viz., Trachysphaera corcyraea (Verhoeff, 1900), T. cristangula (Attems, 1943), T. schmidtii Heller, 1858, and T. similicostata (Radu & Ceuca, 1951), all new to the fauna of the country, as well as T. costata (Waga, 1857a) and T. lobotarsus (Attems, 1943). All of these species are richly illustrated and mapped. To verify the identity of some species, historical material from the Natural History Museum in Vienna, including syntypes, is also studied, and two lectotypes have been designated. Some misidentifications from the literature have been corrected. Trachysphaera acutula (Latzel, 1884) syn. n., T. cultrifera (Verhoeff, 1906) syn. n. and T. multiclavigera (Verhoeff, 1898) syn. n. are all considered as junior subjective synonyms of T. schmidtii. Trachysphaera attemsi Golovatch, 1976 syn. n. is transferred from the list of synonyms of T. costata to the list of synonyms of T. corcyraea. One species, T. similicostata, is resurrected from synonymy. Relationships between some congeners and the taxonomic problems within the genus are briefly discussed.